2018
DOI: 10.1016/j.tins.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Glucocorticoids and Memory for Substance Use

Abstract: The biological stress response of the body forms one of the foundations of adaptive behavior, including promoting (and impairing) different forms of memory. This response transcends stressful experiences and underlies reactions to challenges and even reinforcers such as addictive substances. Nevertheless, drug-induced stress responses are rarely incorporated into models of addiction. We propose here that drug-induced stress responses (particularly glucocorticoids) play a crucial role in addictive behavior by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 159 publications
(201 reference statements)
2
19
0
Order By: Relevance
“…Memories of past experiences can be brought to mind by incidental reminders, such as external stimulus (or internal stimulus [85,86] e.g., stress [6]). At a neural level, partial reactivation of activity patterns formed during the initial experience can lead to reactivation of all of the pattern.…”
Section: Learning Historymentioning
confidence: 99%
See 2 more Smart Citations
“…Memories of past experiences can be brought to mind by incidental reminders, such as external stimulus (or internal stimulus [85,86] e.g., stress [6]). At a neural level, partial reactivation of activity patterns formed during the initial experience can lead to reactivation of all of the pattern.…”
Section: Learning Historymentioning
confidence: 99%
“…When context memories are not recalled, decisions may be swayed by the first memory that comes to mind [18]. Suggestively, recent work has shown that memory recall prioritizes events with highly salient, surprising rewards [114][115][116]-which may describe early, positive drug experiences; and that stress may cue retrieval of past stressful occasionswhich, in SUD populations, may include or cause drug use [6,85]. Together, these findings support two routes by which acute stress may influence memory retrieval and yield relapse: (a) diminishing retrieval of drug-inconsistent context memories, leaving initial drug-related memories to guide behavior; and (b) promoting retrieval of drug-consistent context memories and hence drug memories themselves.…”
Section: Spiraling Into Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we demonstrated, this was the site that showed a significant difference in methylation status after the Bonferroni correction. This may be of vital importance since glucocorticoids mediate nervous system functions in substance dependency [ 35 ]. In response to this, we concluded that hindering glucocorticoid responses could change drug-induced reactions, including the modulation of drug-related learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting recent account proposes that the influence of stress on substance-seeking behaviours could be circular [119,120]. We reviewed evidence suggesting that the stress-induced shift from goal-directed to habitual control relies on the activation of the glucocorticoid system [91][92][93][94], but strikingly, the consumption of addictive substances (e.g., nicotine, cannabis, alcohol, stimulants and opioids) increases the level of glucocorticoids (for a review see [119]). Although this substance-induced increase of glucocorticoid does not correlate with a subjective feeling of negative affect classically experienced under stress, it has been proposed that it contributes to the consolidation of cue-response memories supporting habitual learning and cue-affect memories supporting Pavlovian learning.…”
Section: The Influence Of Stress On Relapsementioning
confidence: 99%